PERAN PENTING CITA RASA DAN KUALITAS PRODUK DALAM MEMBANGUN MINAT BELI KONSUMEN UMKM KACANG MERAH WIRA BAJING KLUNGKUNG - Meryawan, I Wayan; Idayanti, I Dewa Agung Ayu Eka; Armi Susanti, Ida Ayu Ketut Lissa (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2023)
The sustainability of MSME businesses can be measured from the level of purchasing power of the products produced. High consumer buying interest reflects the success of a product that can be accepted by consumers and indirectly has an impact on the resilience of MSMEs in the business sphere. High buying interest can occur if the taste and quality of the products produced can meet consumer expectations. MSMEs Kacang Merah Wira Bajing Klungkung has product taste and product quality that still needs to be improved in creating consumer buying interest in the products produced. This study, the main purpose of analyzing the influence of taste and product quality on consumer buying interest. Accidental sampling became a reference for the selection of research samples with a total of 96 consumers, data was collected through the distribution of questionnaires with validity tests. Test the hypothesis using multiple regression tests, determination, F test and t test. The first hypothesis can be proven by the results of racial aspirations and product quality has a significant influence on buying interest, as well as the second and third hypotheses can be proven by the results of taste and product quality have a positive and significant influence on buying interest. The results of this study provide reinforcement that the taste and quality of products can increase consumer buying interest, especially MSME products.